2020
DOI: 10.1016/j.celrep.2020.107994
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEK1/2 Forestalls the Onset of Acquired Resistance to Entrectinib in Multiple Models of NTRK1-Driven Cancer

Abstract: NTRK1 gene fusions are actionable drivers of numerous human malignancies. Here, we show that expression of the TPR-NTRK1 fusion kinase in immortalized mouse pancreatic ductal epithelial (IMPE) (pancreas) or mouse lung epithelial (MLE-12) cells is sufficient to promote rapidly growing tumors in mice. Both tumor models are exquisitely sensitive to targeted inhibition with entrectinib, a tropomyosin-related kinase A (TRKA) inhibitor. Initial regression of NTRK1-driven tumors is driven by induced expression of BIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Off-target mechanisms can develop during TRK inhibitor treatment, which include genomic alterations of downstream pathway mediators and other receptor tyrosine kinases ( Figure 2 ). Preclinical study showed that the reactivation of RAF-MEK-ERK signaling was observed in NTRK1-driven pancreatic cancer and lung cancer treated with entrectinib, which was possibly one of the acquired-resistance mechanisms to entrectinib, and combined inhibition of TRKA plus MEK1/2 markedly forestalled the onset of drug resistance in both models ( 85 ). Furthermore, BRAF V600E mutation, KRAS G12D mutations, and MET amplifications were also identified as the bypass-mediated resistance mechanisms to TRK inhibitors for patients with NTRK fusions.…”
Section: Trk Inhibitors and Resistancementioning
confidence: 99%
“…Off-target mechanisms can develop during TRK inhibitor treatment, which include genomic alterations of downstream pathway mediators and other receptor tyrosine kinases ( Figure 2 ). Preclinical study showed that the reactivation of RAF-MEK-ERK signaling was observed in NTRK1-driven pancreatic cancer and lung cancer treated with entrectinib, which was possibly one of the acquired-resistance mechanisms to entrectinib, and combined inhibition of TRKA plus MEK1/2 markedly forestalled the onset of drug resistance in both models ( 85 ). Furthermore, BRAF V600E mutation, KRAS G12D mutations, and MET amplifications were also identified as the bypass-mediated resistance mechanisms to TRK inhibitors for patients with NTRK fusions.…”
Section: Trk Inhibitors and Resistancementioning
confidence: 99%
“…Understanding the factors underlying intrinsic/acquired resistance to this new class of compounds is critical, in particular for CRC patient benefit. There is a growing body of evidence suggesting that deficient apoptosis induction following targeted therapy treatments can lead to a lack of efficacy (37, 38). Indeed, we found that KRAS G12C inhibitor monotherapy was relatively ineffective at inducing apoptosis in vitro in KRAS G12C MT CRC.…”
Section: Discussionmentioning
confidence: 99%
“…21 Silencing of BIM, downstream of the MAPK pathway, contributed to resistance to entrectinib in 2 new TPR-TRKA driven mice models in pancreatic and lung cancer. 22 In these models, vertical inhibition using entrectinib 1 cobimetinib (an MEK inhibitor) delayed the onset of resistance to entrectinib. Thus, upfront dual targeting of the implicated pathways may delay the emergence of resistant tumor clones and lead to more durable disease control compared with monotherapy.…”
Section: Discussionmentioning
confidence: 99%